ANALISIS OPTIMALISASI PENGELOLAAN DANA DESA DALAM UPAYA PENANGANAN STUNTING DI DESA PAGUTAN, KECAMATAN BATUKLIANG, KABUPATEN LOMBOK TENGAH: Analysis Of Village Fund Management Optimization In An Efforts To Handl Stunting In Pagutan Village, Batukliang District, Central Lombok Regency - Rahmandari, Ismi Arifiana; Putra, Sandi Justitia; Sujudi, Anis; Sumanjayadi, Sumanjayadi (Ganec Swara, 2025)
This study aims to analyze the optimization of Village Fund management in efforts to address stunting in Pagutan Village, Batukliang District, Central Lombok Regency, in the 2019–2021 period. Village Fund management for the stunting program includes planning, implementation, administration, reporting, and accountability in accordance with the Minister of Home Affairs Regulation Number 20 of 2018. This study uses a qualitative approach with descriptive methods through in-depth interviews with stakeholders, observation, and documentation studies. The results show that the management of Village Funds for stunting management has been implemented in accordance with regulations and is supported by a fairly good level of transparency through the dissemination of APBDes information to the community. However, the effectiveness of the program is still hampered by weak coordination between the Village Government and the Regional Government, as well as low levels of trust in Posyandu cadres regarding the management of activity funds. This study recommends improving coordination between levels of government, developing integrated strategies, and strengthening community participation to encourage transparency, accountability, and optimizing the use of Village Funds in reducing stunting rates sustainably